Well-being of Mangrove Crab Fishermen Households Assisted by Fisheries Extension Officers in Sorong City - Hendra Poltak; Muhfizar Muhfizar; Handayani Handayani; Endang Gunaisah; Matahari Matahari (LPPM Politeknik Saint Paul Sorong, 2023)
Well-being, viewed from a social aspect, is a condition in which individuals feel comfortable, peaceful, happy, and able to meet their living needs while being free from various burdens and difficulties. This research aims to determine the well-being of mangrove crab fisherman households in Sorong City. The survey method is employed, utilizing both primary and secondary data. Primary data is obtained through questionnaires filled out by 69 respondents who are mangrove crab fishermen, while secondary data is obtained from relevant literature sources related to the research topic. Stratified random sampling is used as the data collection technique. The collected data is analyzed using well-being indicators that encompass income, expenditure, living conditions, family members' health, and access to education and transportation. The research findings indicate that the majority of mangrove crab fisherman households in Sorong City, based on the well-being indicators from BPS (2016), are classified as prosperous.